(untitled) (Economic and Political Thought, 2024)
The Eastern Partnership Program is one of the main instruments of the EU foreign policy to regulate relations with third countries. The program includes six states of Eastern Europe and the South Caucasus - Armenia, Azerbaijan, Belarus, Georgia, Moldova, and Ukraine. This initiative contributes to the intensification of political and economic relations between the European Union and the above-mentioned countries. Eastern Partnership Program focuses on sustainable development, rule of law, digital transformation of the economy, and “shaping a green economy” among other areas. A new instrument designed for the EU foreign policy was presented, such an instrument: “Global Europe/Neighborhood, Development and International Cooperation Instrument (NDICI)”. The plans and programs outlined in the Global Europe instrument are fully in line with the post-2020 policy of the European Union’s Eastern Partnership.